Plasma Assisted Flame Stabilizationin a Non-Premixed Lean Burner. (December 2015) - Giorgi, Maria Grazia De; Sciolti, Aldebara; Campilongo, Stefano; Pescini, Elisa; Ficarella, Antonio; Martini, Luca Matteo; Tosi, Paolo; Dilecce, Giorgio
Abstract: In recent years, the application of plasma actuators in different engineering fields was considered particularly interesting. It was successfully applied for the cold flow control in aero engines and turbo-devices. One important application concerns the use of non-equilibrium plasma for plasma-assisted ignition and combustion control. The reduction of nitric oxides (NOx) in aircraft engines, gas turbines, or internal combustion engines has become a major issue in the development of combustion systems. A way to reduce the NOx emissions is to burn under homogenous lean conditions. However, in these regimes the flame becomes unstable and it leads to incomplete combustion or even extinction. Thus, the major issue becomes to stabilize the flame under lean conditions. In this context the present work aims to demonstrate the possibility to increase the combustion efficiency of a lean flame through the use of nanosecond repetitively pulsed plasma (NRPP). A NRPP produced by electric pulses with amplitude up to 40 kV, pulse rise time lower than 4 ns and repetition rate up to 3.5 kHz has been used to stabilize and improve the efficiency of a lean non premixed methane/air flame in a non-premixed Bunsen-type burner. The burner is optically accessible permitting the imaging acquisitions of the flame region. The flame behavior was acquired using a high rate CCD camera in order to capture the differences between the baseline conditions and the actuated cases. Moreover a post-processing technique showing the jagging of the flame in different conditions was applied to evaluate the changes occurring in presence of plasma actuation in term of flame area weighted respect to the luminosity intensity. It was shown that the plasma significantly allows stabilizing the flame under lean conditions where it would not exist without plasma.